Boundary Condition for Dislocation Dynamic Simulation in BCC Crystal (CSIAM Transactions on Applied Mathematics, 2021)
The movement of dislocations and the corresponding crystal plastic deformation are highly influenced by the interaction between dislocations and nearby freesurfaces. The boundary condition for inclination angle $θ$inc which indicates the relationbetween a dislocation line and the surface is one of the key ingredients in the dislocation dynamic simulations. In this paper, we first present a systematical study on $θ$inc by molecular static simulations in BCC-irons samples. We also study the inclinationangle by using molecular dynamic simulations. A continuum description of inclination angle in both static and dynamic cases is derived based on Onsager's variationalprinciple. We show that the results obtained from continuum description are in goodagreement with the molecular simulations. These results can serve as boundary conditions for dislocation dynamics simulations.